Computational analysis of static height stability and aerodynamics of vehicles with a fuselage, wing and tail in ground effect. (15th November 2018) - Lee, Juhee
Abstract: Wing-in-ground (WIG) effect vehicles skim the surface of the ground or water using an air cushion between the vehicle and the surface. The lift augmentation and drag reduction are considerable compared to an airplane flying out of ground effect and significantly enhance the aerodynamic performance. However, the stability problem is still a challenge for researchers and designers of WIG effect vehicles. In a previous study, sectional shapes were optimized for the wing-in-round effect (WIG) using computational fluid dynamics (CFD) and multi-objective optimization with two objectives: the aerodynamic center of height, which is part of the static height stability, and the lift-to-drag ratio. The optimization study obtained 113 optimal solutions called Pareto optima or Pareto sets, which include various airfoil profiles such as a flat lower surface and a convex lower surface next to the trailing edge. In this study, some of the Pareto optima that show the characteristics of features in the design domain are selected, and are applied to a three-dimensional vehicle with a fuselage, lifting and control surfaces such as a horizontal tail. Three featured optima that show high stability, high performance, and relatively stable cases are carefully investigated using computational methods to analyze the aerodynamic characteristics, stability, and three-dimensional effects. Highlights: We performed a numerical analysis of WIG vehicles including a fuselage, wing, and t-tail in ground effect. The optimized wing section obtained our previous study is used for the wing section of this study. Various stability conditions including static height stability, and the location of the center of gravity are discussed. Even thought, a WIG vehicles is a potential transportation advantages, WIG industries are still limited by technical difficulties. Analysis includes aerodynamic characteristics of the three-dimensional flow in ground effect.